Development and assessment of ASTEC-Na fuel pin thermo-mechanical models performed in the European JASMIN project. (September 2018) - Perez-Martin, S.; Pfrang, W.; Girault, N.; Cloarec, L.; Laborde, L.; Buck, M.; Matuzas, V.; Flores y Flores, A.; Raison, P.; Smith, A.L.; Mozzani, N.; Feria, F.; et al.
Highlights: ASTEC-Na fuel pin thermo-mechanical models have been assessed in the JASMIN project. A cladding mechanical model and an in-pin fuel relocation model have been developed. ASTEC-Na predictions for 4 CABRI transient tests are compared to experimental data. Conclusions on the overall ASTEC-Na fuel pin models performance are presented. Abstract: ASTEC-Na is a computer code system which evaluates protected and unprotected accidents in Sodium-cooled Fast Reactors throughout the Initiation Phase. The fuel pin behavior models implemented in ASTEC-Na simulate the essential aspects of the thermal and mechanical behavior of SFR fuel pins in nominal and accidental conditions. Besides the improvement of existing ASTEC-Na models, a specific cladding mechanical model and an in-pin fuel relocation model have been developed during the JASMIN project, where the latter has been already implemented in the code. ASTEC-Na fuel pin behavior models are described in this paper and their transient predictions for four CABRI transient tests are compared to available experimental data as well as to SAS-SFR and SIMMER-III code calculations. Conclusions on the overall performance of ASTEC-Na fuel pin models are also presented.